Analysis of Culinary Business Development Strategies in The Perspective of Islamic Ethics (Case Study In Ms. Djito Batu's Catering Ambassador Business) - Ajat Sudrajat (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2023)
The potential for culinary business development in Malang City is growing rapidly, one of which is in the catering business sector. More than 100 catering businesses in Malang prove that this business is in great demand by the people of Malang City. One of the catering businesses located in Malang City is Duta Catering, Ms. Djito, which is located between the border of Malang City and Batu City. Catering Ambassador Ms. Djito is one of the best catering businesses and is ranked No. 01. For the city of Malang and No. 02 for all East Java Province. Of course, achieving this is not an easy thing, but Catering Ambassador Ms. Djito has strategies for developing her business, and they are analyzed using Islamic Ethics. From the in-depth research findings, it can be seen that the strategy used by Ambassador Catering, Mrs. Djito, uses 3 strategies. Namely vertical integrity strategy (forward integrity strategy, backward integrity strategy, and horizontal integrity strategy), intensive strategy (market penetration strategy and product development strategy), and diversification strategy implementing a related/concentric diversification strategy. If analyzed with Islamic ethics, the strategies implemented by Catering Ambassador Ms. Djito are in general in accordance with the existing theory. In this case the Catering Ambassador, Ms. Djito, does not only focus on strategies in general, but the Catering Ambassador, Ms. Djito, also does not forget matters regulated by the Islamic Religion